2022
DOI: 10.1021/acsomega.2c03848
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber/Phenolic Composites with High Thermal Conductivity Reinforced by a Three-Dimensional Carbon Fiber Felt Network Structure

Abstract: The formation of highly thermally conductive composites with a three-dimensional (3D) oriented structure has become an important means to solve the heat dissipation problem of electronic components. In this paper, a carbon fiber (CF) felt with a 3D network structure was constructed through the airflow netting forming technology and needle punching. The carbon fiber/phenolic composites were then fabricated by CF felt and phenolic resin through vacuum impregnation and compression molding. The effects of CF felt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In addition, some CFs boast a high axial TC of up to 1100 W/(mK) along the axial direction, and their TC is <10 W/(mK) along the radial direction. 28,29 TCPCs with randomly filled CFs do not show promising TC values. It has been reported that the TC of randomly CF-filled (20 wt%) polydimethylsiloxane (PDMS) composites was only 1.3 W/(mK).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, some CFs boast a high axial TC of up to 1100 W/(mK) along the axial direction, and their TC is <10 W/(mK) along the radial direction. 28,29 TCPCs with randomly filled CFs do not show promising TC values. It has been reported that the TC of randomly CF-filled (20 wt%) polydimethylsiloxane (PDMS) composites was only 1.3 W/(mK).…”
Section: Introductionmentioning
confidence: 90%
“…However, CFs have anisotropic TCs. In addition, some CFs boast a high axial TC of up to 1100 W/(mK) along the axial direction, and their TC is <10 W/(mK) along the radial direction 28,29 . TCPCs with randomly filled CFs do not show promising TC values.…”
Section: Introductionmentioning
confidence: 98%
“…Carbon–phenolic materials are not good thermal insulators but act as excellent ablators [ 11 ]. The poor thermal insulation, which is characterized by high thermal conductivity, makes carbon–phenolic materials ideal for improving heat dissipation in electronic components [ 12 ]. On the contrary, for the spacecraft heat shield applications, the thermal insulation provided by carbon–phenolic materials needs to be improved to protect the metallic frame of the spacecraft, as the commonly used high-temperature resistant aluminum alloys begin to lose their strength above 473.15 K (i.e., 200 °C) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being excellent ablators, carbon-phenolic materials are considered poor thermal insulators [1]. The poor thermal insulation, which is a result of high thermal conductivity, makes carbon-phenolic materials favorable for enhancing heat dissipation in electronic components [16]. However, for spacecraft heat shield applications, the poor thermal insulation of carbon-phenolic materials is unfavorable.…”
Section: Introductionmentioning
confidence: 99%